2016
DOI: 10.1002/jat.3357
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans model in toxicity testing

Abstract: Caenorhabditis elegans is a small nematode that can be maintained at low cost and handled using standard in vitro techniques. Unlike toxicity testing using cell cultures, C. elegans toxicity assays provide data from a whole animal with intact and metabolically active digestive, reproductive, endocrine, sensory and neuromuscular systems. Toxicity ranking screens in C. elegans have repeatedly been shown to be as predictive of rat LD50 ranking as mouse LD50 ranking. Additionally, many instances of conservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
284
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(291 citation statements)
references
References 87 publications
(110 reference statements)
1
284
0
6
Order By: Relevance
“…The nematode C. elegans was used to test the toxicity of SiC nanoparticles since basic physiological processes and stress responses are conserved between this nematode and humans (Lee et al, 2007;Hunt, 2017). We used the L1 of C. elegans since several reports showed that L1 is more sensitive than both L4 and young adult of C. elegans to nanoparticles such as Al nanoparticles and others (Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nematode C. elegans was used to test the toxicity of SiC nanoparticles since basic physiological processes and stress responses are conserved between this nematode and humans (Lee et al, 2007;Hunt, 2017). We used the L1 of C. elegans since several reports showed that L1 is more sensitive than both L4 and young adult of C. elegans to nanoparticles such as Al nanoparticles and others (Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some are restricted to a specific geographical environmental condition while others are ubiquitous (Hodda, 2011). The bacterial feeding nematode Caenorhabditis elegans is a well-known multicellular model organism and is used extensively in toxicity assessment studies (Ma et al, 2009;Hunt, 2017). Meloidogyne incognita, a plant parasitic nematode belonging to the root knot nematodes family (RKN), was also challenged with several nanoparticles, such as silver, titanium, and silicon nanoparticles (Ardakani, 2013;Cromwell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Nanomaterials obtained from different sources produced different results in mouse lung exposed by inhalation. 27 Recently, zebra fish (Danio rerio) 39 and Caenorhabditis elegans 40,41 have been used as in vivo models for nanoparticle toxicity testing. Meyer et al 42 showed the uptake and growth inhibition of three silver nanoparticles with different sizes and polyvinylpyrrolidone or citrate coatings using C. elegans.…”
Section: In Vivo Toxicity Of Nanomaterialsmentioning
confidence: 99%
“…Caenorhabditis elegans (C. elegans), a globally distributed, soil-inhabiting nematode species, [2] has been widely utilized as a model organism in research studies due to factors such as its low cost, ease of cultivation and maintenance, short generation time, the large number of eggs per adult, the availability of numerous genetically modified versions of the species, 60 % to 80 % gene homology to humans, and its optical transparency. [3,4] Additionally, they feed by taking in surrounding media and suspended particles via a pharyngeal pumping mechanism, [5] making them especially ideal organisms for nano-uptake and nanotoxicity studies.…”
Section: Principles and Scopementioning
confidence: 99%